Composing an Adhesion Barrier Using Hyaluronic Acid and Carboxymethylcellulose to Prevent Mediastinal Adhesion - Akkuş, Ali Murat; Demirkaya, Ahmet; Erşen, Ezel; Şimşek, Fatma; Ramazanoğlu, Rana; Öz, Büge; Kaynak, Kamil (Cerrahpaşa Medical Journal, 2023)
Objective: Remediastinal interventions is an indispensable procedure to assess mediastinal lymph node metastasis after induction chemotherapy in patients with non-small cell lung cancer. Remediastinal interventions can be a difficult procedure because adhesions of a prior mediastinoscopy may reduce surgeon’s field of view, and may cause difficulty in diagnosing a lymph node, which causes suspicion about invasion. There are several adhesion barrier procedures, which were used to prevent postoperative adhesions, but none of them provided remarkable results. There are studies including abdominal, gynecologic and neurochirurgic surgery, however, there is no sufficient study regarding mediastinum. In this study, we are going to explore the role of hyaluronic acid and carboxymethylcellulose in preventing mediastinal adhesion. Methods: In our study, 21 New Zealand-type male and female rabbits – each with a weight of 2500-3500 grams – were used. Three groups – each including seven rabbits – were set up due to randomized sampling method. Mediastinal dissection was performed in the first group and Seprafilm® was used to build adhesion inhibition. Mediastinal dissection was performed in the second group and 0.9 % NaCl was used to build adhesion inhibition. In the control group, all layers were sutured primarily after mediastinal dissection. The rabbits were sacrificed after 30 days and each group was compared with the control group, using macroscopic and microscopic adhesion criteria. Results: According to the results of our study, Seprafilm® was found to be statistically efficient in preventing and decreasing adhesion in mediastinum (p<0.01 in macroscopic criteria, p<0.05 in inflammation and vascular proliferation criteria). Conclusion: Seprafilm® can be used as an adhesion barrier in prevent of adhesions which develop as a result of surgery.